2013
DOI: 10.1159/000354844
|View full text |Cite
|
Sign up to set email alerts
|

Donor Satisfaction with a New German Blood Donor Questionnaire and Intention of the Donor to Return for Further Donations

Abstract: <b><i>Background:</i></b> The aim of this study was to describe donor satisfaction regarding different aspects of the new German blood donor questionnaire (BDQ) and to assess whether donor satisfaction is associated with the intention to return for further donations. <b><i>Methods:</i></b> A random number of 6,600 blood donors, donating at the German Red Cross Blood Service Baden-Wuerttemberg - Hessen, were asked to rate their satisfaction with four different asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
(29 reference statements)
2
10
1
1
Order By: Relevance
“…In Germany, a uniform DHQ was introduced (for voluntary use), which addressed sexual behavior directly to avoid donors' self-assessment of their infection risk. Pre-evaluation studies showed a higher percentage of correct answers about sexual risk behavior [19] compared to the established DHQs, but a notable portion of donors considered those questions as too personal [20,21]. However, it was also shown that questions dealing with sexual risk behaviors were accepted -despite the discomfort -if the questions were demonstrated to potentially increase blood safety [20].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, a uniform DHQ was introduced (for voluntary use), which addressed sexual behavior directly to avoid donors' self-assessment of their infection risk. Pre-evaluation studies showed a higher percentage of correct answers about sexual risk behavior [19] compared to the established DHQs, but a notable portion of donors considered those questions as too personal [20,21]. However, it was also shown that questions dealing with sexual risk behaviors were accepted -despite the discomfort -if the questions were demonstrated to potentially increase blood safety [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nach ihrer Rückkehrintention gefragt, äußerten besonders viele SpenderInnen (89,7%), dass sie sehr wahrscheinlich wiederkehren werden. Zwar war auch in vergangenen Befragungen die Rückkehrintention stets sehr ausgeprägt gewesen, vor allem bei erfahrenen SpenderInnen 26 . Im Frühjahr 2020 war sie allerdings – sowohl bei erfahrenen SpenderInnen, als auch bei ErstspenderInnen – besonders hoch.…”
Section: Spenderinnen Die Auch Während Einer Pandemie Spendenunclassified
“…This raised concern that -apart from the additional deferrals -some donors might refrain from donating and even dissuade others from donating due to the felt private nature of the NDQ. This effect was addressed in two studies: In the first study a random sample of 6,600 donors were asked to participate in a mail survey and to rate satisfaction with the NDQ as well as the intention to return for further donations [41]. The participants were asked to answer scaled questions about format and layout of the DQ, clarity of the questions, the scope of the questionnaire, and their perception of the questions about sexual risk behavior.…”
Section: Additional Donor Questionnaire Studiesmentioning
confidence: 99%